Dampak Penerapan Strategi Digital Marketing Pada Bisnis Fashion Heypearl Store - Adistya Pramudyana; Budi Prabowo (Institut Teknologi dan Bisnis Semarang, 2023)
In today's digital era, the internet is very helpful in facilitating daily work. Likewise in the field of marketing, both direct and indirect product marketing. Having the right marketing strategy can help companies increase profits and avoid losses, one of which is caused by inefficient and effective promotions. This study aims to determine the impact of implementing the digital marketing strategy used by Heypearl Store. This study uses a qualitative descriptive approach and the subject is Heypearl Store. The results of observations, documents, and interviews will be the source of data. Based on the results of the analysis and discussion, the implementation of the digital marketing strategy by the Heypeal Store is by using an optimized website, utilizing the marketplace, being active on social media, and implementing an SEO strategy. So the impact of implementing these implementations is that HeyPearl Store Surabaya can expand reach, increase product visibility, and reach the target audience more effectively. All this contributes to increasing product sales and strengthening brand presence in the digital market.